(untitled) - Heymann, Jody (Boston, Mass., 2010)
Featuring cases from companies around the globe, this book shows how real organizations are excelling financially by strengthening frontline employees' working conditions.
Keywords: Personnel management,Quản trị nhân sự; United States,Mỹ